CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION: NEW ASPECTS OF THE DEVELOPMENT AND PROGRESSION OF THE DISEASE - A. A. Klimenko; N. A. Shostak; N. A. Demidova; I. V. Novikov (Klinicist)
The review presents data on the incidence of chronic thromboembolic pulmonary hypertension after pulmonary thromboembolism and describescongenital and acquired coagulation abnormalities in patients with venous thromboembolism. It considers the potential factors of development of chronic thromboembolic pulmonary hypertension and some medical conditions and diseases, which favors the development of pulmonary hypertension after prior pulmonary thromboembolism.